2008
DOI: 10.1109/tbme.2008.918565
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Imaging of Bioimpedance Distribution by Means of Current Reconstruction Magnetic Resonance Electrical Impedance Tomography

Abstract: We have developed a novel magnetic resonance electrical impedance tomography (MREIT) algorithm-current reconstruction MREIT algorithm-for noninvasive imaging of electrical impedance distribution of a biological system using only one component of magnetic flux density. The newly proposed algorithm uses the inverse of Biot-Savart Law to reconstruct the current density distribution, and then, uses a modified J-substitution algorithm to reconstruct the conductivity image. A series of computer simulations has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 29 publications
0
24
0
1
Order By: Relevance
“…The entity model, forward FE model and cross-section view of the inverse FE model for the external MREIT study are shown in figure 1. In the present study, two bipolar rectangular currents (Gao et al 2006, 2008) were injected from E1 to E3 and from E2 to E4, respectively. A number of research results reported that a current density of 2 A/m 2 is safe for the human body below 3 kHz (Giland et al 2007, Dalziel 1972).…”
Section: Computer Simulationmentioning
confidence: 99%
“…The entity model, forward FE model and cross-section view of the inverse FE model for the external MREIT study are shown in figure 1. In the present study, two bipolar rectangular currents (Gao et al 2006, 2008) were injected from E1 to E3 and from E2 to E4, respectively. A number of research results reported that a current density of 2 A/m 2 is safe for the human body below 3 kHz (Giland et al 2007, Dalziel 1972).…”
Section: Computer Simulationmentioning
confidence: 99%
“…Ansätze zur Rekonstruktion der Stromdichte J aus dem gemessenen (diskretisierten) Magnetfeld lassen sich grob, in diskrete und kontinuierliche Verfahren, unterteilen [6]. Im diskreten Ansatz wird J als Ströme durch diskrete Leitungsstücke mit diskreten Flächen modelliert, die in einem Gitter angeordnet sind [1]. Kontinuierliche Verfahren betrachten das Gesetz von Biot-Savart hingegen als Faltungsintegral, mit der vom Messabstand h x abhängigen Green- Funktion G(x -x , y -y ), das über die Fourier-Transformation im Frequenzbereich gelöst werden kann [3; 8].…”
Section: Rekonstruktion Der Stromdichte Junclassified
“…However, similar to EIT, the surface measurements and ill-posedness of the inverse problem result in low spatial resolution. 3) Magnetic Resonance Electrical Impedance Tomography (MREIT), which originates from Magnetic Resonance Current Density Imaging (MRCDI) [30], [31], measures the local magnetic field induced by surface current injection, and reconstructs static cross-sectional conductivity images [32]–[35]. While MREIT provides high spatial resolution, what remains to be demonstrated includes the safety issues due to the usage of high level of current injection in order to achieve sufficient SNR, and the shielding effect due to the use of surface electrodes for current injection.…”
Section: Introductionmentioning
confidence: 99%